Search for heavy resonances decaying to two Higgs bosons in final states containing four b quarks - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (European Physical Journal C: Particles and Fields, 2016)
A search is presented for narrow heavy resonancesX decaying into pairs of Higgs bosons (H) in protonprotoncollisions collected by the CMS experiment at theLHC at √s = 8 TeV. The data correspond to an integratedluminosity of 19.7 fb−1. The search considers HH resonanceswith masses between 1 and 3 TeV, having final states of twob quark pairs. Each Higgs boson is produced with largemomentum, and the hadronization products of the pair ofb quarks can usually be reconstructed as single large jets.The background from multijet and tt events is significantlyreduced by applying requirements related to the flavor of thejet, its mass, and its substructure. The signal would be identi-fied as a peak on top of the dijet invariant mass spectrum of theremaining background events. No evidence is observed forsuch a signal. Upper limits obtained at 95 % confidence levelfor the product of the production cross section and branchingfraction σ (gg → X) B(X → HH → bbbb) range from 10to 1.5 fb for the mass of X from 1.15 to 2.0 TeV, significantlyextending previous searches. For a warped extra dimensiontheory with a mass scaleR = 1 TeV, the data exclude radionscalar masses between 1.15 and 1.55 TeV.